PENGARUH POSISI BAUT GALVANIS DAN STAINLESS STEEL DITINJAU DARI FRACTURE SURFACE PADA SAMBUNGAN PLAT - Nofriady Handra; Brazi Brazi (Jurnal Teknik Mesin (JTM), 2012)
This study is an experimental study using the UTM (Universal Testing Machine) where the bolts are the main object of the test. Testing independent variables are used only in the varying positions. Testing was conducted using 3 (three) bolts located at the 5 (five) pieces in a jig (test tool of the shear bolts), with different positions for each test. Number of bolt position is that as many as 5 variations of the entire position will be obtained in the optimal position to receive style. Objectives to be achieved is to know the phenomena that occur in the process of loading on the bolts. Besides the above objectives, this study also to identify and analyze the characteristics of the material properties of the shear plate is fastened with two bolts, on a variety of positions so we get a position that would result in fracture or shear bolt receiving optimal shear forces. Optimal position to receive a shear force is position 2 and 3. The position is not optimal receive shear force is position 4